Influence of daily consumption of synbiotic soy-based product supplemented with okara soybean by-product on risk factors for cardiovascular diseases - Bedani, Raquel; Rossi, Elizeu Antonio [UNESP]; Umbelino Cavallini, Daniela Cardoso [UNESP]; Pinto, Roseli Aparecida [UNESP]; Vendramini, Regina Célia; Augusto, Elaine Moura; Parra Abdalla, Dulcinéia Saes; Isay Saad, Susana Marta (Elsevier B.V., 2015)
This study aimed to investigate the effect of a synbiotic fermented soy product supplemented with okara (a by-product from soybean) on cardiovascular disease risk markers in healthy men. In a randomized, double-blinded, placebo controlled trial, thirty-six normocholesterolemic men were assigned to two groups. Subjects consumed daily 100 g of soy-based product fermented with Lactobacillus acidophilus La-5, Bifidobacterium animalis subsp. lactis Bb-12, and Streptococcus thermophilus (starter culture) (synbiotic group - S) (n = 18) or 100 g of unfermented soy-based product (placebo group - P) (n = 18) for 8 weeks. Fasting blood samples and anthropometric measurements were collected at the baseline (To), the end of week 4 (T-4), and the end of week 8 (T-8). Serum lipids, C-reactive protein, fibrinogen, and electronegative LDL were also analysed on To, T-4, and T-8. During the period of daily soy-based product consumption (from To to T-8) the LDL-C mean decreased significantly (p < 0.05) in groups, resulting in a significant (p < 0.05) improvement of the LDL-C/HDL-C ratio. Comparing mean differences (T-8-T-0) between the two groups, the trend of LDL-C and LDL-C/HDL-C ratio reductions was higher in group S (14.1 mg/dL and 038 mg/dL, respectively) than group P (4.9 mg/dL and 0.17 mg/dL, respectively) (p > 0.05). Our results suggest limited lipid-lowering effects of synbiotic soy-based product supplemented with okara on cardiovascular risk markers in normocholesterolemic men. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Fermented soy product; Lactobacillus; Bifidobacterium; Inulin; Okara; Cardiovascular risk markers